PPSG: science boot camp “promoting science through experience” - Mohamadin, Mohammad Isa (UiTM Sarawak, 2016)
The Bachelor in Science Chemistry Student Association and lecturers under Pusat Pengajian Sains Gunaan, UiTM Sarawak organized a one-day Science Boot Camp for 60 primary school students from Kota Samarahanarea. The camp was held at Samarahan 2campus on 10th November 2015. The standard 4, 5 and 6 students were from SK Pinang, SK Meranek, SK Mata Parang, SK Dato Traoh and SK Kampung Melayu. The camp aimed to expose the students to the science experiments in real laboratories.